2016
DOI: 10.5937/ratpov53-9761
|View full text |Cite
|
Sign up to set email alerts
|

Fruit traits of pepper genotypes originating from open pollination

Abstract: Summary:In different regions of Serbia people consume pepper fruits with various shapes, sizes and colors. In southern Serbia consumers prefer longer fruits, while in the northern part shorter fruits are more preferred. The aim of this paper was to evaluate four pepper genotypes (355, 356, 357, and 358) with shorter fruits originating from open pollination. These genotypes were compared with the parental line 354 with longer fruits. The fruits were harvested in technological maturity. Fruit (length, width, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…Pepper comparing to other vegetable species (without potatoes) has the first rank in Serbia with 16,977 ha in 2016 (STATISTICAL OFFICE OF THE REPUBLIC OF SERBIA, 2017). In different regions of Serbia, consumers are preferred to use pepper fruits with various shapes, sizes and colors (DANOJEVIĆ et al, 2016). In Serbia, beside of fresh use, pepper usually used as roasted, stuffed (with various fillings), pickled, dried, ground, ajvar, pindjur and processed in many different ways (DANOJEVIĆ et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pepper comparing to other vegetable species (without potatoes) has the first rank in Serbia with 16,977 ha in 2016 (STATISTICAL OFFICE OF THE REPUBLIC OF SERBIA, 2017). In different regions of Serbia, consumers are preferred to use pepper fruits with various shapes, sizes and colors (DANOJEVIĆ et al, 2016). In Serbia, beside of fresh use, pepper usually used as roasted, stuffed (with various fillings), pickled, dried, ground, ajvar, pindjur and processed in many different ways (DANOJEVIĆ et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…U Republici Srbiji paprika je jedna od najznačajnijih povrtarskih vrsta, ali se navike potrošača u odnosu na oblik, veličinu i boju ploda paprike razlikuju u zavisnosti od regiona . U južnim delovima Srbije potrošači više vole duže plodove paprike, dok u severnom delu Srbije (Vojvodina) kraće (Danojević et al ., 2016) . Kao rezultat oplemenjivačkog rada na paprici u Institutu za ratarstvo i povrtarstvo dobijeno je nekoliko sorti slatke paprike u tipu babure kao što su: Novosadska bela babura, Atina, Anita i Vranjska .…”
Section: Uvodunclassified
“…Međutim plodovi sorte Matice rastu uspravno na biljci, kao i kod odomaćene blago ljute sorte Somborke (Danojević et al ., 2017) . U sortimentu Instituta se ne nalazi nijedna sorta slatke paprike sa konusnim i visećim plodovima (Danojević et al ., 2016), pa su oplemenjivački napori usmereni u tom pravcu kako bi se mogla ponuditi tržištu nova sorta koja će imati viseće plodove, svetlo žute boje i krupnije od sorte Matice .…”
Section: Uvodunclassified
“…Zečević (2001) found that FD, FL, PT, number of fruits and FW are in a strong positive correlation. In the previous research the positive correlation of FW, FD and PT to TSS was noted, probably because of different breeding material and the fact that those fruits were harvested at technological maturity (Danojević et al 2016).…”
mentioning
confidence: 92%
“…Comparing to other vegetable species (apart from potato), in term of production area, pepper has the first rank in Serbia with 16,977 ha in 2016 (Statistical Office of the Republic of Serbia, 2017). Consumers in different parts of Serbia prefer pepper fruits of various shapes, sizes and colours and it has a great range of use in Serbia (Danojević et al, 2016). Besides the fresh consumption, pepper is usually used as roasted, stuffed (with various fillings), pickled, dried, ground, and processed in many different ways (Danojević et al, 2017a).…”
mentioning
confidence: 99%